2012
DOI: 10.1126/science.1219379
|View full text |Cite
|
Sign up to set email alerts
|

Rad51 Is an Accessory Factor for Dmc1-Mediated Joint Molecule Formation During Meiosis

Abstract: Meiotic recombination in budding yeast requires two RecA-related proteins, Rad51 and Dmc1, both of which form filaments on DNA capable of directing homology search and catalyzing formation of homologous joint molecules (JMs) and strand exchange. Using a separation-of-function mutant form of Rad51, that retains filament-forming but not JM forming activity, we show that the JM activity of Rad51 is fully dispensable for meiotic recombination. The corresponding mutation in Dmc1 causes a profound recombination defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

38
433
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 296 publications
(473 citation statements)
references
References 30 publications
38
433
0
2
Order By: Relevance
“…However, if nutrients reappear in the environment prior to the end of prophase, the meiotic program is aborted and cells return smoothly to the mitotic cell cycle, carrying out a regular mitotic division in which intact sister chromatids segregate regularly to opposite poles. Recently, in vivo studies have revealed a strong dependence of Dmc1 activity on Rad51 (Cloud et al, 2012;Hong et al, 2013). A DSB preferentially selects a homolog partner in both Rad51-and Dmc1-promoted recombination, in the absence or presence of the meiotic axis components Red1/Mek1/Hop1.…”
Section: Discussionmentioning
confidence: 99%
“…However, if nutrients reappear in the environment prior to the end of prophase, the meiotic program is aborted and cells return smoothly to the mitotic cell cycle, carrying out a regular mitotic division in which intact sister chromatids segregate regularly to opposite poles. Recently, in vivo studies have revealed a strong dependence of Dmc1 activity on Rad51 (Cloud et al, 2012;Hong et al, 2013). A DSB preferentially selects a homolog partner in both Rad51-and Dmc1-promoted recombination, in the absence or presence of the meiotic axis components Red1/Mek1/Hop1.…”
Section: Discussionmentioning
confidence: 99%
“…Work in Saccharomyces cerevisiae and Arabidopsis has established that Rad51 is needed for Dmc1 filament formation, and one model posits that Rad51 serves to initiate a Dmc1 filament (4,21,22). In our previous work, we showed that BRC1-4 bind with high affinity to free RAD51, enhancing ssDNA assembly and limiting its nucleation on dsDNA, resulting in a stimulation of DNA strand exchange.…”
Section: Brca2 Stimulates the Dna Strand Exchange By Dmc1 Overcomingmentioning
confidence: 99%
“…Rad51 and Dmc1 share ~45% amino acid identity (6,8,9), they assembly into structurally similar right-handed helical filaments on single-stranded DNA (ssDNA) (10)(11)(12), and they have similar, albeit not identical, biochemical properties (1,6). Despite these many commonalities, Dmc1 is the recombinase responsible for performing strand invasion during meiosis (13). In contrast, Rad51 is actively downregulated by Hed1-and Mek1-mediated inhibition of its interactions with Rad54, which is a cofactor that is required for Rad51 strand invasion activity (11,(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%